The Throwing Shoulder: The Common Injuries and their Underlying Mechanisms - Gyftopoulos, Soterios; Recht, Michael (Seminars in Musculoskeletal Radiology, 2014)
The mechanics of the throwing shoulder are complex, resulting in a variety of adaptations that can lead to increased performance for the athlete. These adaptations can eventually fail and result in pathology to the stabilizing structures of the shoulder, most notably the rotator cuff and glenoid labrum. The understanding of the relationship between the mechanisms and injuries is evolving, resulting in improved diagnostic, therapeutic, and preventative measures. Our goal is to clarify the relationship between the mechanisms, common types of injury, and their appearance on imaging, specifically MRI, in a comprehensive, easy-to-understand manner that will leave you more confident when evaluating this subset of patients.
Keywords: SLAP tear; GIRD; internal impingement